The Impact of Fingerprints on BPJS Patient Registration Speed and Identity Accuracy - Ma Clara Yureka W I; Joan Puspita Tanumihardja; Falentina Faustin Ngode; Martina Klaudia (Journal of Innovative and Creativity, 2026)
Outpatient services are a service unit with a high volume of visits, thus demanding a fast and accurate registration system. Manual registration still often results in long queues, service delays, and the risk of patient identification errors, potentially opening up opportunities for fraud in BPJS Kesehatan services. As an effort to improve service effectiveness, the BLUD RSUD dr. T.C. Hillers Maumere has implemented a fingerprint biometric verification system in all outpatient polyclinics since 2021. This study aims to assess the impact of fingerprint use on service speed and identity accuracy of outpatient BPJS patients. The study used a descriptive quantitative design with a population of all outpatient BPJS patients and a sample of 154 respondents determined using the Slovin formula. The sampling technique was accidental sampling. The research instrument was a Guttman scale questionnaire that measured registration speed, ease of use, and perceptions of identity accuracy. Data analysis was conducted descriptively using frequency distributions and percentages. The results showed that 96 percent of respondents stated that fingerprints accelerated the registration process, 97 percent considered this system to prevent identity errors, and 91 percent felt it reduced queues. The majority of users were from the productive age group and housewives, indicating good acceptance of the technology among non-digital natives. Thus, fingerprints have proven to be an effective innovation in supporting the acceleration of services and increasing the accuracy of outpatient BPJS patient administration.